Critical Thinking Skills of Students in Response Political News on Social Media Instagram - Asep Anggi Dikarsa; Aim Abdulkarim; Muhamad Halimi (Journal of International Conference Proceedings (JICP), 2020)
The purpose of this research was to determine the critical thinking skills of students in response to political news on social media instagram. This research is motivated by the lack of interest and also not caring of students to political news on social media instagram. In addition, the tendency of students do not have the ability to understand the political news on social media instagram. This study uses a qualitative method with case study design. Based on the research, the obtained data as well as the finding that students' critical thinking skills in response to political news on instagram social media can be in the form and grow up through the study of the discussion, as well as with political education and political literacy.